DETERMINATION OF OPTIMAL PARAMETERS OF A WET CLEANING DEVICE (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In the article, based on the results of the experimental study, the optimal values of the parameter in the experimental device of the drum wet dust cleaning device are determined. Assuming that the effect of variable factors is fully explained by a second-order polynomial, the experiments were carried out on the basis of the “Fractional Factorial Experiment” plan.